Protopanaxadiol manipulates gut microbiota to promote bone marrow hematopoiesis and enhance immunity in cyclophosphamide‐induced immunosuppression mice - Yuru Cao; Ben Liu; Wenzhen Li; Feng Geng; Xue Gao; Lijun Yue; Huiping Liu; Congying Liu; Zhenguo Su; Junhong Lü; Xiaohong Pan (MedComm)
Abstract Protopanaxadiol (PPD) has potential immunomodulatory effects, but the underlying mechanism remains unclear. Here, we explored the potential roles of gut microbiota in the immunity regulation mechanisms of PPD using a cyclophosphamide (CTX)‐induced immunosuppression mouse model. Our results showed that a medium dose of PPD (PPD‐M, 50 mg/kg) effectively ameliorated the immunosuppression induced by CTX treatment by promoting bone marrow hematopoiesis, increasing the number of splenic T lymphocytes and regulating the secretion of serum immunoglobulins and cytokines. Meanwhile, PPD‐M protected against CTX‐induced gut microbiota dysbiosis by increasing the relative abundance of Lactobacillus, Oscillospirales, Turicibacter, Coldextribacter, Lachnospiraceae, Dubosiella, and Alloprevotella and reducing the relative abundance of Escherichia‐Shigella. Importantly, PPD‐M lost the ability to promote bone marrow hematopoiesis and enhance immunity when the gut microbiota was depleted by broad‐spectrum antibiotics. Moreover, PPD‐M promoted the production of microbiota‐derived immune‐enhancing metabolites including cucurbitacin C, l‐gulonolactone, ceramide, DG, prostaglandin E2 ethanolamide, palmitoyl glucuronide, 9R,10S‐epoxy‐stearic acid, and 9′‐carboxy‐gamma‐chromanol. KEGG topology analysis showed that the PPD‐M treatment significantly enriched the sphingolipid metabolic pathway with ceramide as a main metabolite. Our findings reveal that PPD enhances immunity by manipulating gut microbiota and has the potential to be used as an immunomodulator in cancer chemotherapy.